DIVERSITY OF STONY CORALS IN BANGGAI WATER - Siringoringo, Rikoh Manogar; Hadi, Tri Aryono (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2013)
Banggai waters, located in Central Sulawesi Province, is part of the worldâ??s coral triangle area which is wellâ??known to have the highest diversity on stony corals (Scleractinia). A research on stony corals has been carried out at 9 study sites between Juneâ??July 2011, practicing line transect methods and free collection in order to determine the recent condition and diversity of the given coral group. The average of live corals coverage was recorded at 46%(ranging between 24â??77%), and categorized as fair condition. The number of coral species found was 194, distributed in 54 genera. The Banggai waters condition was considered good and potential to sustain the coralsâ??growth. Even though so, in several particular areas, there were still threats on coral reefs.